2023
DOI: 10.1038/s41746-023-00750-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of digital technology in surgical home hospital programs

Abstract: Home hospital (HH), a care delivery model of providing hospital-grade care to patients in their homes, has become increasingly common in medical settings, though surgical uptake has been limited. HH programs have been shown to be safe and effective in a variety of medical contexts, with increased usage of this care pathway during the COVID-19 pandemic. Though surgical patients have unique clinical considerations, surgical Home Hospital (SHH) programs may have important benefits for this population. Various tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Another study shows that the use of a non-contact video camera to monitor vital signs can be used to track early signs of physiological deterioration, to function as a less disruptive, more efficient, early warning system 20 . These new capabilities may enable an eventual shift in the nucleus of post-surgical care from the hospital back to the home; some large academic medical centers have already established successful digital technology-enabled surgical home hospital programs that allow patients to be safely recover from surgery in their own home 21 .…”
Section: Emerging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study shows that the use of a non-contact video camera to monitor vital signs can be used to track early signs of physiological deterioration, to function as a less disruptive, more efficient, early warning system 20 . These new capabilities may enable an eventual shift in the nucleus of post-surgical care from the hospital back to the home; some large academic medical centers have already established successful digital technology-enabled surgical home hospital programs that allow patients to be safely recover from surgery in their own home 21 .…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…For example, few studies have shown any improvement in care when AI-enabled decision support tools are used 29 . Some important barriers to clinical impact include translating ML model outputs into clinically actionable insights and incorporating them into existing workflows and clinical decision making processes 15 , 21 , 30 . Additionally, these new technologies must be built and rigorously evaluated in a way that is reproducible, transparent, and interpretable to users to earn their trust 30 , 31 .…”
Section: Emerging Technologiesmentioning
confidence: 99%